If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = -23 Reorder the terms: 7 + 3x = -23 Solving 7 + 3x = -23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = -23 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = -23 + -7 3x = -23 + -7 Combine like terms: -23 + -7 = -30 3x = -30 Divide each side by '3'. x = -10 Simplifying x = -10
| 5x+4=-16 | | -3x-4=17 | | -5x+4=21 | | -5+4=21 | | -4x+9=49 | | -4+9=49 | | -2x+5=17 | | y=2x+5 | | 2y-26+19=8y-60-5 | | 6x-3=51 | | 7x-8=41 | | 6(y-12)+12=4(2y-15)-24 | | 4x-3=29 | | (x-4)(x+5)=10 | | 5x+2=37 | | 2(4t-5)+t=40-t | | 2(y-13)+19=4(2y-15)-5 | | 2x-3x+8=18-6x | | y=(x-(x-(.20))) | | 108=(x-(x-(0.20))) | | 2(x+1)-3x=3(3+2x) | | bird*8= | | 88x=32x | | 36x=36x | | t(5t+4)=0 | | 16a+11b+20a= | | 0=-15m | | 64z-31-(91+19z)= | | 24+9x=-3 | | 4x+2y-7(4x-7y+3z)= | | 8(y+2)=2(3y+4) | | x*x= |